The water sensitive city - Grant, Gary, 1958- (Chichester, West Sussex, United Kingdom : Wiley, 2016)
"This book advocates a more thoughtful approach to urban water management. The approach involves reducing water consumption, harvesting rainwater, recycling rainwater and adopting Sustainable Drainage Systems (SuDS) where surface water is not sent straight to drains but is intercepted by features like green roofs, rain gardens, swales and ponds.Cities in particular need to change the existing linear model of water consumption and use to a more circular one in order to survive. The Water Sensitive City brings together the various specialised technical discussions that have been continuing for some time into a volume that is more accessible to designers (engineers and architects), urban planners and managers, and policymakers"--
"This book advocates a more thoughtful approach to urban water management, including for example, exponents of the Water Sensitive Urban Design (WSUD) approach in Australia and Low Impact Development in the US. This new approach involves reducing water consumption, harvesting rainwater, recycling rainwater and adopting Sustainable Drainage Systems (SuDS) where surface water is not sent straight to drains but is intercepted by features like green roofs, rain gardens, swales and ponds. This water sensitive approach conserves water, reduces flooding, cleans water (and therefore streams, rivers and seas). It is compatible with the greener city and green infrastructure agendas, whereby policy makers want to make cities more liveable. This subject matters because the current use of water by cities is unsustainable. Cities in particular need to change the existing linear model of water consumption and use to a more circular one in order to survive. Aquifers all over the world, including some that have taken millions of years to form, are predicted to dry up in the coming decades. Reservoirs, eg Lake Mead near Las Vegas once believed to have permanently solved water supply problems, are falling to dangerously low levels. This book is needed in order to bring together the various specialised technical discussions that have been continuing for some time into a volume that is more accessible to designers (engineers and architects), urban planners and managers, and policymakers. People need to understand that urban water management should increasingly become their concerns rather than a technical matter to be addressed by specialists alone"--
Machine generated contents note: About the Author Acknowledgement 1. Water & Cities 2. A Brief History of Water Supply & Sanitation 3. Demand 4. Supply 5. Climate Change & Water 6. Microclimate 7. Ecosystem Approach 8. Rivers & Coasts 9. Near-Natural Drainage 10. Reduce 11. Collect 12. Recycle 13. Water Quality 14. Future Water Sensitive Cities Useful resources.
Includes index.
Architecture
Keywords: Municipal water supply; Water-supply -- Management; Water demand management; Urban ecology (Biology); Urban ecology (Sociology); BUSINESS & ECONOMICS / Development / Sustainable Development